Hubungan Pendekatan Humanistik Untuk Meningkatkan Kreativitas Siswa Dalam Bahasa Inggris - Nur Hasan; Dwi Nur Hadiyansah Wijaksono S (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2021)
In this modern era, more and more researchers were interested in the factors causing the increased creativity of students in the classroom, and experts still do not get a definite factor or aspect in increasing student creativity. students in class. based on a significant level of 5% with 23 respondents, the rxy value was smaller than in the table (0.024 < 0.413), so the null hypothesis was accepted, while the working hypothesis was rejected, it means that this research was non-significant. So, it can be concluded that there was no relationship between the humanistic relationship with the creativity of students in the classroom.